O LUGAR DAS IDEIAS LIBERAIS NAS MEMÓRIAS PÓSTUMAS DE BRÁS CUBAS - Couto, Elvis Paulo [UNESP] (Universidade de São Paulo - Faculdade de Filosofia, Letras e Ciências Humanas, 2020)
In his well-known book, A Master on the Periphery of Capitalism, Roberto Schwarz shows that the predominant formal principle, the volubility of the first-person narrator, in Machado de Assis's The Posthumous Memoirs of Brás Cubas was created to critically and ironically expose how Brazil was acclimating to liberalism. In addition to questioning the sociological implication of this argument, this paper aims to discuss the representation of liberal ideas in Machado's novel from the perspective that underlines the triumph of liberalism in the literary imagination.

Em seu conhecido livro Um mestre na periferia do capitalismo, Roberto Schwarz mostra que o princípio formal predominante do romance Memórias póstumas de Brás Cubas, de Machado de Assis - a volubilidade do narrador em primeira pessoa -, foi criado com vistas a expor crítica e ironicamente a aclimatação do liberalismo no Brasil. Este artigo, além de questionar a implicação sociológica desse argumento, visa a discutir a representação das ideias liberais no romance machadiano sob a perspectiva que salienta o triunfo do liberalismo no plano da imaginação literária.
THE PLACE OF LIBERAL IDEAS IN THE POSTHUMOUS MEMOIRS OF BRÁS CUBAS
Keywords: Machado de Assis; The Posthumous Memoirs of Brás Cubas; liberalism; Machado de Assis; Memórias póstumas de Brás Cubas; liberalismo